Comorbidity among Hospitalized Patients with Chronic Obstructive Pulmonary Disease in a Teaching Hospital, West Java Indonesia - Aini, Dini Qurrotu; Suryadinata, Hendarsyah; Herdiningrat, R. B. Soeherman (Althea Medical Journal, 2015)
Background: One of the most important causes that can increase the risk of hospitalization and death inÂ chronic obstructive pulmonary disease is comorbidity. The aim of this study was to identify the proportion of comorbidity among hospitalized patients with chronic obstructive pulmonary disease in a teaching hospital, West Java, Indonesia, from January to December 2012.Methods: A descriptive study was conducted fromÂ September to November 2013 in Internal Medicine Department of Dr. Hasan Sadikin General Hospital Bandung. The study used 107 medical records that consisted of data about patients with chronic obstructive pulmonary disease (COPD) who were hospitalized between January to December 2012. The medical records were collected using simple random sampling. Variables identified in this study were characteristics of the patients (age, sex, and smoking history) and comorbidity events. Comorbidity events were coronary artery disease (CAD), lung cancer, diabetes mellitus (DM) type 2, anemia, dyslipidemia, osteoporosis, depression, pulmonary artery hypertension (PAH), andhypertension. Age variable was divided into 3 categories with interval 20 years. All collected data were presented in frequency distribution.Results: Most of the patients in this study were 50â69Â years old, male, and had smoking history. The highest proportion of comorbid condition was hypertension, followed by anemia and coronary artery disease.Conclusions: Patients with COPD have one or more other diseases (comorbidity). Three most frequent comorbidities are hypertension, anemia, and coronary artery disease. [AMJ.2015;2(4):485â91]Â DOI:Â 10.15850/amj.v2n4.632